Comparison of Maternal and Neonatal Outcomes between Vaginal Delivery and Cesarean Section under General or spinal anesthesia- retrospective study - Ali Karami; Sara Khademi; Zeinabsadat Fattahi Saravi; Reza Jouybar; Zahra Esmaeilinezhad; Elham Asadpour (Mashhad University of Medical Sciences, 2020)
Introduction: World Health Organization (WHO) has reported that the exact impacts of cesarean section on maternal and neonatal health are uncertain. This study was performed with aim to compare maternal and neonatal outcomes after vaginal delivery, cesarean section with general anesthesia or spinal anesthesia. Methods: In this retrospective study, 122 medical records of women who underwent vaginal delivery and non-emergency cesarean section at Ghadir Mother and Child Hospital affiliated to Shiraz University of Medical Sciences in 2015-2016 were divided into three groups of 36 subjects (vaginal delivery, cesarean section with general anesthesia and spinal anesthesia) were evaluated. Maternal heart rate and blood pressure, Apgar score, and fetal blood gas of umbilical cord were assessed. Data were analyzed by SPSS software (version 19) and One-way ANOVA test was used for parametric data between groups and repeated measure for evaluating the effect of time in the groups. P Results: Exact Apgar scores at 1 and 5 min showed no significant difference between the groups (P = 0.39 and P = 0.91, respectively). Fetal pH was higher in cesarean group with spinal anesthesia (P = 0.05) while PO2 and HCo3 were higher in cesarean group with general anesthesia (P = 0.04). Postpartum systolic blood pressure in women under spinal anesthesia and diastolic blood pressure in women under general anesthesia were significantly different with other two groups (P <0.05). Conclusion: Postpartum systolic blood pressure was higher in women under spinal anesthesia and diastolic blood pressure was higher in women under general anesthesia than other groups. pH of the infant's blood was higher in the cesarean group with spinal anesthesia, and the oxygen and bicarbonate pressure in the umbilical cord blood of the infants was higher in the cesarean group with general anesthesia, but the Apgar score and carbon dioxide pressure did not differ between the groups.